Tissue distribution of esterase isozymes and their responses to cypermethrin in three macrobrachium species - Rashid, Md Abdur; Begum, Rowshan Ara; Shahzahan, Reza Md (Journal of the Asiatic Society of Bangladesh, Science, 2013)
In recent times prawn grounds are getting contaminated with an increased use of agricultural pesticides. Esterases play an intermediary role in conferring or in contributing to insecticide resistance. Hence, Esterase isozyme variability was studied in three Macrobrachium species (M. rosenbergii, M. malcolmsonii and M. lamarrei) on 7.5% PAGE with ? and ? naphthyl acetate as substrate in terms of number of bands, staining intensity and toxicity effects. Expression of esterase isozymes was studied in five different tissues (eye, muscle, nerve cord, stomach and hepatopancreas) where four esterase bands (Est-1, Est-2, Est-3 and Est-4) were observed in M. rosenbergii and M. lamarrei and two bands (Est-1 and Est-4) in M. malcolmsonii. Bands in the hepatopancreas of M. rosenbergii, in the eye of M. lamarrei and in the nerve cord of M. malcolmsonii were highly intense indicating higher esterase activity. It was also noticed that the slowest bands with higher molecular weight were more expressed than the others and spreading area of a particular band was not fixed in all the tissues. To observe the impact of insecticide on esterases all five tissues were exposed to 1000 ppm of cypermethrin for 24 hours and was subjected to PAGE, it was found that treated samples showed less esterase expression. Only the muscle tissues from three species were exposed to a range of doses (0.078-1000 ppm), species specific fluctuation of esterase activity was observed in an irregular fashion. Bioassay conducted with cypermethrin on M. lamarrei indicated that LC50 was 0.05ppm at 2 hours. Fluctuation of esterase activity was observed with time and dose concentrations in post mortal electrophoretic assay. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15614 J. Asiat. Soc. Bangladesh, Sci. 38(2): 227-235, December 2012